Normal families of meromorphic functions sharing values or functions - Jiang Yunbo (Journal of Inequalities and Applications, 2011)
Abstract In this paper, we investigate the normal families of meromorphic functions concerning shared values and shared analytic functions and prove some normal criteria that generalize or extend some results obtained by Q. C. Zhang, Y. T. Li and Y. X. Gu, J. M. Chang. Mathematics Subject Classification (2000): 30D45; 30D35.